Os reflexos de uma formação continuada na prática profissional de professores que ensinam matemática - Gualandi, Jorge Henrique (2019)
Mathematics teaching is a field that encompasses both teacher education and professional practices, representing a key activity in the professional development of teachers. This study investigated the impact of a continued education intervention on the professional practice of teachers who teach mathematics. The theoretical focus addressed five aspects: a) continued education of the teacher; b) professional development; c) knowledge held by the teacher; d) professional practice; and e) algebraic thinking. A qualitative approach was adopted based on the stages of didactic engineering (as construed by Artigue), applying this to the steps in a mathematics investigation (as defined by Ponte, Brocardo, and Oliveira). The study involved 20 teachers who taught mathematics at municipal schools within a county of Espírito Santo State, Southeast Brazil. Data were collected via semi-structured interviews and by observing teachers while they solved tasks on pattern generalization, and were also drawn from their records, compiled texts on the subject, and written or sound-recorded reports of the tasks produced or adapted by the teachers for use with students. The results showed that the continued education intervention allowed the teachers to explore a wide variety of elements, demonstrating changes in their professional practice: a) change in lesson organization and planning; b) change in classroom organization; c) change in approach to tasks involving pattern generalization; d) change in interest for reading material related to mathematics education; e) change in approach to posing and solving problems in the classroom; f) change by adopting an active role in the teaching and learning process. Also, the results of the investagion yield a positive assessment of the role that continuing education can play in teacher learning